On consideration of radiated power in RF field simulations for MRI - Liu, Wanzhan; Kao, Chien-ping; Collins, Christopher M.; Smith, Michael B.; Yang, Qing X. (Magnetic resonance in medicine, 2013)
In numerical analyses of radiofrequency (RF) fields for MRI, RF power is often permitted to radiate out of the problem region. In reality, RF power will be confined by the magnet bore and RF screen enclosing the magnet room. We present numerical calculations at different frequencies for various surface and volume coils, with samples from simple spheres to the human body in environments from free space to a shielded RF room. Results for calculations within a limited problem region show radiated power increases with frequency. When the magnet room RF screen is included, nearly all the power is dissipated in the human subject. For limited problem regions, inclusion of a term for radiation loss results in an underestimation of transmit efficiency compared to results including the complete bore and RF screen. If the term for radiated power is not included, calculated coil efficiencies are slightly overestimated compared to the complete case. Magn Reson Med, 2013. © 2012 Wiley Periodicals, Inc.